Mobili: Development and Use of a Usability Checklist for Mobile Games and Applications - Carneiro, Nayana; Melo, Bianca; Cavalcante, Letícia; Castro, Rute; Andrade, Rossana M. C.; Darin, Ticianne (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2020)
Given the expansion of the Brazilian mobile development market and its dynamic context, it is essential to use interaction design and evaluation methods that suit the industry's needs and allow companies to design high-quality applications while continuously evolving them. The present work reports our experience of developing the Mobili checklist and applying it within a software development project. Mobili offers guidance in conducting heuristic evaluations in mobile games and applications, and it was applied to assist in identifying priority corrections and evolutions for the software products developed in our project. Thus, this paper aims to share lessons that can be useful for teams in similar contexts.